Between Global Aspirations and Developmental Considerations: Pre-service Teachers’ Beliefs about English Instruction in Indonesian Early Childhood Education - Maesaroh, Dwi Titi; Bhakti, Sektalonir Oscarini Wati (Faculty of Education and Teacher Training of UINSI Samarinda, 2026)
This research examines the beliefs of pre-service early childhood education (ECE) teachers in Indonesia regarding the integration of English in early childhood environments. As English becomes more important around the world, people are starting to wonder where it fits into early learning environments and whether future teachers are ready to teach it. Using a qualitative descriptive approach, data were gathered from six pre-service teachers via open- and closed-ended questionnaire responses and analyzed thematically. The results indicate that participants predominantly perceive English as essential for children's future communicative competencies and global involvement. At the same time, their answers show that they are being careful: most people think that English should be an extracurricular subject rather than a core part of the curriculum, which shows that children's developmental stages should come first. Participants stressed how important it is for young learners to have simple, contextual vocabulary and fun ways to learn. They also voiced worries about the teachers' abilities, how well they pronounced words, and how little help they got from the school. The study indicates that although pre-service teachers are favorably disposed towards early English instruction, they remain cognizant of both practical and pedagogical challenges. These insights highlight the necessity of enhancing teacher preparation programs and offering more explicit policy guidance to facilitate developmentally appropriate English instruction in Indonesian early childhood education settings.